Synchronization of Leishmania amazonensis Cell Cycle Using Hydroxyurea - Oliveira, Beatriz C. D. de [UNESP]; Assis, Luiz H. C. [UNESP]; Shiburah, Mark E. [UNESP]; Paiva, Stephany C. [UNESP]; Fontes, Veronica S. [UNESP]; Oliveira, Leilane S. de [UNESP]; Silva, Vitor L. da [UNESP]; Silva, Marcelo S. da [UNESP]; Cano, Maria Isabel N. [UNESP] (Springer Nature, 2022)
Leishmania spp. comprises a group of protozoan parasites that affect millions of people around the world. Understanding the main cell cycle-dependent events could provide an important route for developing specific therapies since some factors involved in cell cycle control may have low similarity relative to their homologs in mammals. Furthermore, accurate cell cycle-dependent analyses often require many cells, which can be achieved through cell cycle synchronization. Here, we described a useful method to synchronize procyclic promastigote forms of Leishmania amazonensis using hydroxyurea (HU) and the analysis of its DNA content profile. This approach can be extended to other trypanosomatids, such as Trypanosoma cruzi or Trypanosoma brucei, and provides an effective method for arresting more than 80% of cells at the G1/S phase transition.
Keywords: Cell cycle synchronization; DNA content profile; Hydroxyurea; Leishmania amazonensis